A review on change propagation approaches in evolvable software - Ibrahim, Noraini (2007)
Abstract Managing changes in the evolutionary software development is inevitable to ensure software remains useful to organization and meet their user expectations. Hence, the task is very labor-expensive, error-prone and tedious process. In general, all software artifacts are related and depend to each other. The relationships and dependencies between the artifacts are established and consistent until one of the links is broken due to the changes introduced.